Development of potato peeling machine - Mohamad Syahmi, Shahrom (2008)
This thesis deals with durability assessment for development of potato peeling machine. The study of manufacturing was very important in order to carried out this project to ensure that student understand on what are needs to do. This project is about development of potato peeling machine to help people easy to use at home. This project involved the process of sketching and drawing. Three sketching will be developing from my idea. After that matrix chart and Pugh analysis will be following to get a new final design. After design had complete, the next process is fabrication to transform from the paper to become real product. This project also require to ensure the safety for the indeed of publishing. Methods and process involve in this project like welding, shearing, cutting, drilling and rivet. This project is mainly about generating a new concept of portable potato machine and more function. After all process had been done, this potato machine may help us to understand the fabrication and designing process that involved in this project.